2012
DOI: 10.1111/j.1552-6569.2012.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Symptomatic Intracranial Atherosclerosis in Caucasians: A Prospective, Multicenter, Transcranial Doppler Study

Abstract: SIA was identified in almost 10% of patients admitted with symptoms of ACI. These preliminary findings support further collaborative initiatives among stroke physicians to increase the yield of SIA detection in Caucasian patients with ACI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 39 publications
1
44
0
2
Order By: Relevance
“…Diabetes mellitus (DM), hypertension, and hypercholesterolemia have been found independently associated with ICS in previous studies (3,11,(13)(14)(15)(16)(17)(18)(19)(20)(21). The present study aimed to determine the prevalence, risk factors, and prognosis of ICS in our stroke registry.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Diabetes mellitus (DM), hypertension, and hypercholesterolemia have been found independently associated with ICS in previous studies (3,11,(13)(14)(15)(16)(17)(18)(19)(20)(21). The present study aimed to determine the prevalence, risk factors, and prognosis of ICS in our stroke registry.…”
Section: Introductionmentioning
confidence: 89%
“…Tsivgoulis et al found that DM was the strongest predictive factor of ICS (14). Arenillas et al reported that high lipoprotein (a) level and DM were independent markers of a greater extent for ICS (19).…”
Section: Risk Factors Of Icsmentioning
confidence: 99%
See 3 more Smart Citations